Crisis Credit, Employment Protection, Indebtedness, and Risk - Federico Huneeus; Joseph P. Kaboski; Mauricio Larrain; Sergio L. Schmukler; Mario Vera (CESifo GmbH, 2025)
This paper studies how credit guarantee and employment protection programs interact in assisting firms during crises times. The paper analyzes how these government programs influence credit allocation, indebtedness, and risk at both the micro and macro levels. The programs provide different incentives for firms. The low interest rate encourages riskier firms to demand government-backed credit, while banks tend to reject those credit applications. The credit demand outweighs this screening supply response, expanding micro-level indebtedness across the extensive and intensive margins among riskier firms. The uptake of the employment program is not associated with risk, as firms internalize the opportunity cost of reduced operations when sending workers home to qualify for assistance. The employment program mitigates the indebtedness expansion of the credit program by supporting firms and enabling banks to screen firms better. Macroeconomic risk of the credit program would increase by a third without the availability of the employment program.
Keywords: G21; G28; G32; G33; G38; I18; 330; banking; credit demand; credit supply; crises; Covid-19; debt; employment protection; firm risk; macroeconomic risk; public credit guarantees